Current phase relation from graphs and diagrams and application to thick ferromagnetic Josephson junctions. (17th April 2018) - Margaris, I; Paltoglou, V; Flytzanis, N
Abstract: In this work we present a method of representing terms in the current-phase-relation of a ballistic Josephson junction by combinations of diagrams, used in previous work to represent an equivalent of the matching condition determinant of the junction. This is accomplished by the expansion of the logarithm of this determinant in Taylor series and keeping track of surviving terms, i.e. terms that do not annihilate each other. The types of the surviving terms are represented by connected graphs, whose points represent diagrammatic terms of the determinant expansion. Then the theory is applied to obtain approximations of the current-phase relation of relatively thick ballistic ferromagnetic Josephson junctions with non-collinear magnetizations. This demonstrates the versatility of the method in developing approximations schemes and providing physical insight into the nature of contributions to the supercurrent from the available particle excitations in the junction. We also discuss the strong second harmonic contribution to the supercurrent in junctions with three mutually orthogonal magnetization vectors and a weak intermediate ferromagnet.